The cyclical component of the debt brake: Analysis and a reform proposal - Florian Schuster; Max Krahé; Philippa Sigl-Glöckner; Dominik Leusder (Dezernat Zukunft e.V., 2021)
Reforming the debt brake (Schuldenbremse) is often understood to require constitutional change. Frequently overlooked, however, is that a crucial part of the debt brake is governed by ordinary law, namely the cyclical component (Konjunkturkomponente). By allowing for more or less net borrowing depending on the level of economic activity, this component was intended to enable a counter-cyclical fiscal policy, while both limiting and legitimising new spending. Sections 1-7 of this paper assess to what extent it is fulfilling this purpose. We find that the cyclical component in its current form is no longer up to scratch, for four reasons. (1) Contrary to legal requirement, it does not take into account the latest social-scientific research. (2) It relies on an arbitrary notion of the "normal level" of economic activity and as a result delegates too much discretion to civil servants, who are insufficiently legitimised to exercise this discretion. (3) It no longer corresponds to the original intention of the legislators. (4) In the context of the Stability and Growth Pact, it was never intended to be used and implemented as it is in Germany now. To address these shortcomings, sections 8 and 9 outline a reform proposal at the subconstitutional level. We propose amending some of the inputs that go into the calculation of the cyclical component. Instead of largely projecting them forward from historical data, we outline how they could be specified on the basis of what generates sustainable public finances in the long run, namely the full utilisation of economic capacity to raise the long-term growth path. However, this proposal does not address some of the debt brake's more fundamental flaws. It is intended merely as a pragmatic first step towards a more democratic, coherent and sustainable fiscal policy in Germany.
Keywords: 330